APPLICATION OF PRIMARY AND SECONDARY RESISTIVITY PARAMETERS IN EVALUATING AQUIFER POTENTIAL AND VULNERABILITY WITHIN KABBA, NORTH CENTRAL NIGERIA - Hudu, Ayorinde Sule; Fabian, Akpah A.; Kizito, O. Musa; Jacob, B. Jimoh (FUDMA Journal of Sciences, 2024)
The study area depends on groundwater as a major source of potable and healthy water supply. However, its occurrence and quality vary with low yield or abortive borehole drilled in some part. Therefore, there is need to properly investigate the geology and groundwater condition of the area using Vertical Electrical Sounding (VES) and Dar Zarrouk parameters. The different rock types identified are migmatite-gneiss, granite-gneiss, schist, and charnockite. Forty (40) VES was carried out which revealed five to four geo-electric layers. These are top soil, lateritic clay, confining weathered basement, weathered/fractured basement aquifers and fresh basement. The types of curves identified are HA and KQ. The average depth to groundwater is 55.00m, this indicate that borehole should be drilled within or above the average depth to avoid later drying of wells. The value of aquifer resistivity and thickness was used to calculate longitudinal conductance, transverse resistance, hydraulic conductivity and transmissivity. The longitudinal conductance varies from poor to good in protective capacity class and revealed that the groundwater is easily exposed to contamination. The aquifer resistivity, thickness with transverse resistance, hydraulic conductivity, and transmissivity were used to classified the groundwater into different zones. The groundwater potential within the study area varies from low to very good with most of the area having moderate potential zones distributed mainly within the migmatite gneiss and the schist. The study area has fractures that can produce water for domestic, agricultural and industrial purpose and the result can be used for proper management of groundwater resources.
Keywords: Basement Aquifer; Potential; Vulnerability; Kabba; North Central Nigeria